Advance in Tissue Culture for Soybean Improvement in Thailand - Siranut Lamseejan; Peerasak Srinives; Gulvadee Chaiyaprasithi; Chuntana Kongnakhon; Peeranuch Kareeros; Sasithorn Chuakuna (Agriculture and Natural Resources, 1993)
Soybean tissue culture protocols in Thailand are set up by 2 laboratories of Kasetsart University, one in the Department of Applied Radiation and Isotopes, Faculty of Science, and the other in the Department of Agronomy, Faculty of Agriculture, They have developed methods, viz. (1) multiple shoot induction from zyotic embryo (2) somatic embryogenesis from immature cotyledon (3) embryogenic suspension culture, and (4) embryo rescue. Each method can be applied to suit various aspects of soybean improvement in Thailand. Method (1) is employed mainly for propagation purpose. Since the plantlets are not derived through callus, they are true-to-type. Method (2) is utilized to induce and select for mutants developed through somatic embryogenesis. Method (3) is more preferable than method (2) since it enhances contact between embryoids and the selection pressure applied into the medium. This helps selecting the real mutants rather than the escape ones. Method (4) allows a plant breeder to expand the use of soybean germplasm, especially to rescue the embryo from wide crossing, before pod abortion.